Determination of available phosphorus in soils by using a new extraction procedure and a flow injection amperometric system - Jaroon Jakmunee (2018)
A new extraction procedure based on an off-line extraction column was proposed for extracting of available phosphorus from soils. The column was fabricated from a plastic syringe fitted at the bottom with a cotton wool and a piece of filter paper to support a soil sample. An aliquot (50 mL) of extracting solution (0.05 M HCl + 0.0125 M H2SO4) was used to extract the sample under gravity flow and the eluate was collected in a polyethylene bottle. The extract was then analyzed for phosphorus contents by a simple flow injection amperometric system, employing a set of three-way solenoid valves as an injection valve. The method is based on the electrochemical reduction of 12-molybdophosphate which is produced on-line by the reaction of orthophosphate with acidic molybdate and the electrical current produced was directly proportional to the concentration of phosphate in range of 0.1-10.0 mg L-1PO4-P, with a detection limit of 0.02 mg L-1. Relative standard for 11 replicate injections of 5 mg L-1PO4-P was 0.5%. A sample through put of 35 h-1was achieved, with consumption of 14 mg KCl, 10 mg ammonium molybdate and 0.05 mL H2SO4per analysis. The detection system does not suffer from the interferences that are encountered in the photometric method such as colored substances, colloids, metal ions, silicate and refractive index effect (Schlieren effect). The results obtained by the column extraction procedure were well correlated with those obtained by the steady-state extraction procedure, but showed slightly higher extraction efficiency. © 2009 Elsevier B.V. All rights reserved.